MANIFESTASI GEJALA KEJIWAAN DALAM KARYA LUKIS - Rio Irwandi, Drs. Erfahmi, M.Sn., Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2016)
Psychiatric symptom is not considered a dangerous disease for the environment. Psychiatric symptom is a disease that begins with a sense of high levels of stress because the patients are not open about their problems or depression that they cannot solve by themselves to the people or environment around them. Psychiatric symptoms suffered negative element values resulting from environmental factors and family factors that could occur by the lack of attention. The description of behavioral psychiatric symptoms is depicted in painting with the title: Stigma, Doctor, My family, Hallucinations, The loss of a sense of reality, The Life Spirit Staring empty, Recovery is a choice, The sense feel and realize, and Reintegration ".Kata kunci:hasil belajar, pembelajaran Seni rupa,model pembelajaran Problem Solving.